2022
DOI: 10.3390/foods11193042
|View full text |Cite
|
Sign up to set email alerts
|

Lycopene-Loaded Bilosomes Ameliorate High-Fat Diet-Induced Chronic Nephritis in Mice through the TLR4/MyD88 Inflammatory Pathway

Abstract: Chronic kidney disease caused by a high-fat diet (HFD)-induced metabolic syndrome has received widespread attention. Lycopene has a wide range of biological activities and can improve a variety of chronic diseases through anti-inflammatory effects. In this study, HFD-fed mice were used as a metabolic syndrome model to evaluate the protective effect of lycopene in a sustained-release vehicle (bilosomes) in the small intestine against renal injury and to determine whether the TLR4/MyD88 pathway and related metab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 42 publications
1
4
0
Order By: Relevance
“…The inflammatory cytokines IL-1β, IL-6, and IL-10 have an important role in the inflammatory process, in which expression levels and action mechanisms contribute to the comprehension of disease pathogenesis and therapeutic approaches. The TLR4/NF-κB/MyD88 pathway has been recognized as a central link in the pathogenic process of systemic inflammation [29]. In the present study, on the one hand, TLR4/MyD88 activation has been found to be notably upregulated in LPSinduced MH-S cells, leading to increased expression of pro-inflammatory cytokines and related chemokines, including TNF-a, IL-1β, IL-6, and IL-10.…”
Section: Discussionsupporting
confidence: 50%
“…The inflammatory cytokines IL-1β, IL-6, and IL-10 have an important role in the inflammatory process, in which expression levels and action mechanisms contribute to the comprehension of disease pathogenesis and therapeutic approaches. The TLR4/NF-κB/MyD88 pathway has been recognized as a central link in the pathogenic process of systemic inflammation [29]. In the present study, on the one hand, TLR4/MyD88 activation has been found to be notably upregulated in LPSinduced MH-S cells, leading to increased expression of pro-inflammatory cytokines and related chemokines, including TNF-a, IL-1β, IL-6, and IL-10.…”
Section: Discussionsupporting
confidence: 50%
“…Therefore, controlling the level of serum UA within the normal range will help alleviate renal injury. Studies have shown that HFD feeding can lead to HUA and chronic kidney injury in mice, the specific pathological manifestations of which are glomerular atrophy, the proliferation of mesangial cells and mesangial matrix, unclear renal tubule structure, fibrosis, and chronic inflammation [23,24]. In this study, HFD-fed mice treated with RES had less glomerular atrophy and clearer renal tubule structures, as observed by HE staining, while the areas of Masson and PAS-positive staining were reduced, indicating decreased renal fibrosis and mesangial matrix proliferation, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that the bilosystem (either bilosome or biloparticle) is able to increase the solubility and to control the release of the incorporated drug. Furthermore, these data revealed the significant dominance of the bilosystem to enhance the intestinal passage of budesonide, possibly due to the ability of these nanocarriers to improve the intestinal permeability of the encapsulated drugs [42][43][44][45][46][47][48][49][50][51][52][53][54][55][56].…”
Section: In Vitro and Ex Vivo Studiesmentioning
confidence: 97%